1985
DOI: 10.1203/00006450-198506000-00057
|View full text |Cite
|
Sign up to set email alerts
|

37 Assessment of Sleep-Associated HGH Secretion in Normal Children and in Endocrine Disorders

Abstract: Bromocriptine (1.25 mg BID) was administered orally to a 23 year old asymptomatic female with accelerated growth and a parasellar tumor (tissue type unknown). Other forms of therapy were refused. Length increased from 76 to 95 cm (22 cm/yr) and weight increased from 10 to 16.25 kg between ages 13 and 23 months. Bone age was 2 years at a chronolorical age of 18 months. Somatomedin C level was 4.3 Ulml (n=2: normal 0.8 to 2.2 Ulml). Thirteen growth hormone values during overnight monitoring averaged 4.7 ng/ml, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
1988
1988

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This confirms the findings of Finkelstein et al [6] who showed a rise of GH secretion during sleep at the beginning of puberty in a few cases. Bierich et al [1] obtained concordant data in a more recent study. Minuto et al [ 15] evidenced the occurrence of multiple secretory peaks also during waking hours at the beginning of puberty.…”
Section: Discussionsupporting
confidence: 69%
“…This confirms the findings of Finkelstein et al [6] who showed a rise of GH secretion during sleep at the beginning of puberty in a few cases. Bierich et al [1] obtained concordant data in a more recent study. Minuto et al [ 15] evidenced the occurrence of multiple secretory peaks also during waking hours at the beginning of puberty.…”
Section: Discussionsupporting
confidence: 69%
“…However, comparing the highest peaks obtained after arginine to those occurring during sleep, it becomes evident that the nocturnal maxima are much higheralmost twice as high as the values after arginine. 3. Maximum peaks attained during arginine provocative tests for hGH in healthy children.…”
Section: Control Groupmentioning
confidence: 99%